How to Transition from Single‐Gene Pharmacogenetic Testing to Preemptive Panel‐Based Testing: A Tutorial. Issue 3 (6th July 2020) - Marrero, Richard J.; Cicali, Emily J.; Arwood, Meghan J.; Eddy, Elizabeth; DeRemer, David; Ramnaraign, Brian H.; Daily, Karen C.; Jones, Dennie; Cook, Kelsey J.; Cavallari, Larisa H.; Wiisanen Weitzel, Kristin; Langaee, Taimour; et al.
Abstract : There have been significant advancements in precision medicine and approaches to medication selection based on pharmacogenetic results. With the availability of direct‐to‐consumer genetic testing and growing awareness of genetic interindividual variability, patient demand for more precise, individually tailored drug regimens is increasing. The University of Florida (UF) Health Precision Medicine Program (PMP) was established in 2011 to improve integration of genomic data into clinical practice. In the ensuing years, the UF Health PMP has successfully implemented several single‐gene tests to optimize the precision of medication prescribing across a variety of clinical settings. Most recently, the UF Health PMP launched a custom‐designed pharmacogenetic panel, including pharmacogenes relevant to supportive care medications commonly prescribed to patients undergoing chemotherapy treatment, referred to as "GatorPGx." This tutorial provides guidance and information to institutions on how to transition from the implementation of single‐gene pharmacogenetic testing to a preemptive panel‐based testing approach. Here, we demonstrate application of the preemptive panel in the setting of an adult solid tumor oncology clinic. Importantly, the information included herein can be applied to other clinical practice settings.